The Influence of Competence on Employee Performance at PT. Mandiri Primatama in Jakarta - Kumala, Destiana; Mutaufiq, Ali; Supriatal, Supriatal (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This study aims to determine the effect of competence on employee performance at PT Mandiri Primatama in Jakarta.The method used is explanatory research with a sample of 80 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study on the competency variable obtained an average score of 3.77 with good criteria. The employee performance variable obtained an average score of 3.90 with good criteria. Competence has a significant effect on employee performance with the regression equation Y = 16.260 + 0.630X, and a correlation value of 0.710 or strong with a determination of 50.4%. The hypothesis test obtained a significance of 0.000 <0.05.).